Two new species and two new records for cicadas (Hemiptera: Cicadidae) from French Guiana, with an updated faunal list of French Guiana and the first synoptic list for Guyana - Sanborn, Allen F. (Zootaxa, 2023)
Zammara conflutrimacula n. sp. and Fidicinoides ininiensis n. sp. are described as new. The first records of Guyalna polypaga Sanborn, 2019 and Taphura dolabella Sanborn, 2017 are reported for French Guiana. Cicada clarisona Hancock, 1834 nomen nudum, revised status, is shown to be unavailable. The first synoptic list of cicadas for Guyana is provided. The currently known cicada fauna for French Guiana is 73 species, 20 genera, five tribes, and three subfamilies. The known fauna of Guyana is 12 species, nine genera, two tribes and one subfamily.